Political activity among state executives: the effect of Hatch Act Repeal - Pearson, William M.; David S., Castle
The debate over Hatch Acts centres around the effect repeal would have an political involvement of public servants and related by the impact of recision on public service. this study examines the consequences of Hatch Act repeal from the perspective of high level state administrators, reporting executives' estimates of their political activity levels at two intervals: the present and potentially, if state Hatch Acts are repealed. The findings indicate that repeal would result in a significant increase in political activities of state executives. If Hatch Acts are revoked and state executives act according to projections, the goal of a neutral and non partisan public service could be jeopardized. Repruduce
Keywords: Hatch Act Repeal; Civil Service; U.S.A.; Political Activity; Civil Service - U.S.A.